Iptimalisasi pembelajaran Tahfid Optimalisasi Pembelajaran Tahfidz Berbasis IT di Madrasah (Studi Kasus MTSN Kota Probolinggo) - Muhammad Ilham Mauludi; Ulil Hidayah (Journal of Innovative and Creativity, 2025)
This study analyzes the implementation and optimization of Information Technology (IT)-based tahfidz learning at MTsN Kota Probolinggo, a pioneering Islamic junior high school integrating digital platforms into Qur’an memorization instruction. The study purpose was to examine the model of IT-based tahfidz instruction, evaluate its effectiveness in improving students’ memorization quality and quantity, and formulate strategic steps for sustainable optimization. Materials and methods. The research used a qualitative case study approach, focusing on contextual and in-depth data collection through interviews, observation, and documentation. MTsN Kota Probolinggo was selected as the research site due to its early adoption of digital tahfidz learning since 2021, supported by a specially designed Android application and web-based monitoring system integrated with school academic services. Results. The findings show that the use of digital platforms increases learning effectiveness in four areas: (1) improved management efficiency through integrated systems, (2) strengthened stakeholder involvement, particularly parents, through real-time monitoring, (3) enhanced flexibility of memorization submissions via online platforms, and (4) standardized assessment procedures for consistent evaluation. Digital infrastructure such as WiFi, LCD projectors, and sound systems also contributes to a supportive learning environment. Conclusions. Despite challenges related to digital competency and technological dependence, the IT-based tahfidz learning model at MTsN Kota Probolinggo demonstrates strong potential to enhance the quality of Qur’an memorization programs. Ongoing digital training, content enhancement, continuous evaluation, and system integration are crucial for sustainability. This model serves as a best practice for other madrasahs and contributes to advancing the development of digital Islamic education in Indonesia.